Інформаційно-психологічні операції як основна загроза інформаційній безпеці держави - Бартельова, Алла; Рудь, Олена (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Under the conditions of informational society, information becomes the most important resource, which determines the functioning and development of all spheres of social life without exception. That is why in any activity the issue of information security is the main factor that shapes its effectiveness. Informational and psychological special operations (IPSO) are a set of measures to distribute specially prepared information to influence people’s emotions, feelings and behavior. Elements of IPSO include disinformation, propaganda, cyber attacks, exaggeration of certain information or downplaying of other one. Under such conditions, it is important to understand how IPSO are created, recognize them in time and counter them.